Improving Student Learning Outcomes through the Think Pair and Share Model in Learning English Language and Literature - Fredrika, Heny (Pinisi Journal of Education and Management, 2023)
The cooperative learning model of the Think Pair and Share (TPS) type is a "cooperative learning model that was first developed by Professor Frank Lyman and his colleagues at the University of Maryland in 1981. This research is a classroom action research. The research subjects were class XII MIPA 1 students of SMA Negeri Integrated Madani Palu Model, a total of 34 people consisting of 11 men and 23 women. While the research procedure consists of 4 stages, namely: planning, implementation, observation and reflection. Further data analysis is carried out through three stages, namely data reduction, data presentation, and data/conclusion verification. The results of the study show that the Think Pair and Share Model can improve learning outcomes in learning English language and literature for class XII MIPA 1 SMAN Integrated Madani Model Palu, Academic Year 2022/2023